1990
DOI: 10.1590/s0373-55241990000100002
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao conhecimento da biologia do peixe-rei, Xenomelaniris brasiliensis (Quoy & Gaimard, 1824) (Atherinidae), no complexo baía-estuário de Santos e São Vicente, Brasil

Abstract: Através de um programa de amostragem com arrastos de praia no complexo baía-estuário de Santos e São Vicente, de dezembro de 1984 a novembro de 1985, foram capturados 2.632 exemplares do peixe-rei Xenomelaniris brasiliensis. Neste trabalho foram analisados a ocorrência, o crescimento, a relação peso / comprimento, o fator de condição e caracteres merísticos e morfométricos. X. brasiliensis foi capturada durante todo o ano na região, sendo mais abundante no verão e outono; a distribuição foi unimodal e o maior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
2
7
0
5
Order By: Relevance
“…This same growth pattern was observed by Hostim-Silva et al (1995) at Conceição Lagoon (SC), although at Santos (SP) the length/weight relationship was isometric (Paiva-Filho & Giannini, 1990). Bemvenuti (1987) reported that A. brasiliensis can reach about 10 cm within one year, attaining a maximum size of 16.0 cm and a maximum longevity of 2 years.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This same growth pattern was observed by Hostim-Silva et al (1995) at Conceição Lagoon (SC), although at Santos (SP) the length/weight relationship was isometric (Paiva-Filho & Giannini, 1990). Bemvenuti (1987) reported that A. brasiliensis can reach about 10 cm within one year, attaining a maximum size of 16.0 cm and a maximum longevity of 2 years.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, different results were reported by Paiva-Filho & Giannini (1990) in Santos (24 o S). These authors found only one modal class throughout the year and no animals larger than 13.2 cm.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…No entanto, trabalhos que avaliaram a ictiofauna em áreas costeiras no sudeste do Brasil, utilizando diferentes métodos de amostragem, apresentaram riqueza de espécies muito próximas dos valores obtidos em Itaipu. ANDREATA et al (2002) registraram 148 espécies na Baía da Ribeira (RJ), enquanto que PAIVA- FILHO et al (1987), amostrando o complexo baía-estuário de Santos, forneceram uma lista de 140 espécies de peixes.…”
Section: Resultsunclassified